An intensive Alpine climbing expedition and its influence on some anthropometric measurements. Issue 2 (July 1980) - Baker, S. J.
Abstract : The effects of an intensive 4 week Alpine climbing expedition on percentage body fat, absolute body fat and lean body mass was investigated in 14 adult male students. Anthropometric measures were taken on two occasions during the training period prior to the expedition, twice during the expedition and finally eight weeks after the expedition had returned home. There was a 3% reduction in percentage body fat between the first testing occasion and the fourth taken towards the end of the expedition. Over the same interval there was a mean reduction of 2.6 kg in absolute body fat and a reduction in lean body mass of 2.47 kg. All three criterion mean values on the final testing session returned to or exceeded those taken on session one.